2016
DOI: 10.1002/jsfa.7852
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, agronomical and microbiological evaluation of alternative growing media for the production of rapini (Brassica rapa L.) microgreens

Abstract: TF and JKF may be valid alternatives to peat and STG because both ensured a competitive yield, low nitrate content and a similar or higher microbiological quality. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
86
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(134 citation statements)
references
References 26 publications
15
86
3
3
Order By: Relevance
“…Consequently, the single shoot mean fresh weight was highest in red cabbage and lowest for arugula, which had the lowest yield and the highest shoot population density, despite the fact that both Brassica species did not differ in terms of fresh yield. Fresh yield and single-shoot fresh weight values in the present study were comparable or higher than those observed in the case of rapini microgreens grown in a similar growing system with the same standard nutrient solution [59]. Dry matter content was higher in red cabbage, followed by arugula, and red mustard, and observed values were in the same range of values observed for rapini microgreens grown in a greenhouse using a similar growing system and the same standard nutrient solution [59].…”
Section: Microgreens Biometric Response To Zinc (Zn) Enrichmentsupporting
confidence: 82%
See 3 more Smart Citations
“…Consequently, the single shoot mean fresh weight was highest in red cabbage and lowest for arugula, which had the lowest yield and the highest shoot population density, despite the fact that both Brassica species did not differ in terms of fresh yield. Fresh yield and single-shoot fresh weight values in the present study were comparable or higher than those observed in the case of rapini microgreens grown in a similar growing system with the same standard nutrient solution [59]. Dry matter content was higher in red cabbage, followed by arugula, and red mustard, and observed values were in the same range of values observed for rapini microgreens grown in a greenhouse using a similar growing system and the same standard nutrient solution [59].…”
Section: Microgreens Biometric Response To Zinc (Zn) Enrichmentsupporting
confidence: 82%
“…In recent years, microgreens have become increasingly popular as a rich source of vitamins, bioactive compounds, and minerals and have rapidly gained the appellative of "super food" or "functional food" [52][53][54][55][56][57][58][59][60]. Like sprouts, microgreens are a promising crop category for Fe and Zn biofortification [55,57,58].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Amaranthaceae, Apiaceae, and Lamiaceae are also health beneficial, and plants in the Alliaceae and Lamiaceae also produce antimicrobial compounds. Microgreens are usually grown in greenhouses in growing flats containing potting mixes, peat‐based mixes, hydroponic growth medium, or even with recycled textile fiber mats (Di Gioia, De Bellis, Mininni, Santamaria, & Serio, ).…”
Section: Microgreen Productionmentioning
confidence: 99%